Comparative analysis of the bioaccumulation of bisphenol A in the blood serum and follicular fluid of women living in two areas with different environmental impacts - Raimondo, Salvatore; Chiusano, Maria Luisa; Gentile, Mariacira; Gentile, Tommaso; Cuomo, Felice; Gentile, Raffaella; Danza, Domenico; Siani, Laura; Crescenzo, Claudia; Palmieri, Mariangela; Iaccarino, Stefania; Iaccarino, Mirella; et al. (Frontiers in Endocrinology, 2024)
Introduction Bisphenol A (BPA) is a common contaminant widely used in many industrial sectors. Because of its wide use and dispersion, it can be accumulated in living human bodies through both oral assumption and nondietary routes. BPA exhibits hormone-like properties, falling under the class of endocrine disruptors; therefore, it can alter relevant physiological functions. In particular, in women, it can affect folliculogenesis and therefore reproduction, contributing not only to infertility, but also to endometriosis and premature puberty. Methods We conducted a multicenter study on 91 women undergoing a first in vitro fertilization (IVF) treatment in the Campania region (Southern Italy). We investigated the presence and concentration of BPA in serum and follicular fluids to assess the effects of airborne BPA contamination. The analysis was conducted on 32 women living in a low environmental impact (LEI) area, from the Sele Valley River and Cilento region, and 59 women living in a high environmental impact (HEI) area, the so-called “Land of Fires”, a highly contaminated territory widely exposed to illegal waste practices. Results A higher average BPA content in both blood serum and follicular fluid was revealed in the HEI group when compared with the LEI group. In addition, we revealed higher average BPA content in blood serum than in folliclular fluid in the HEI area, with opposite average content in the two fluids in the LEI zone. In addition, our results also showed a lack of correlation between BPA content in follicular and serum fluids both in the overall population and in the HEI and LEI groups, with peculiar trends in different subsets of women. Conclusion From our results, we revealed a heterogeneity in the distribution of BPA content between serum and follicular fluid. Further studies are needed to unravel the bioaccumulation mechanisms of BPA in highly polluted and nonpolluted areas.